Acting out and enactment: An effort at clarity. Issue 1 (2nd January 2022) - Bettelheim, Eric C.
ABSTRACT: Acting out and enactment are terms in widespread use colloquially and in psychoanalytic psychotherapy to describe patient and therapist behavior. Both terms are poorly defined in the literature and have varied in interpretation as theoretical frameworks have changed. The advent of relational and inter-personal therapeutic approaches has blurred both the distinction between talking and action established by Freud and the boundaries of clinical practice. A review of the history of both terms reveals their core meaning as transgressive; by one of the analytic pair or by both, respectively. Behavior violating therapeutic boundaries and the analytic attitude, including those triggered by countertransference, are important indicators of repressed trauma as Freud originally thought. His retreat from the seduction theory led to the confusion of acting out with transference and to later authors confusing enactment with countertransference. Traumatic memories are uniquely stored and difficult to recover and characterized by hypofunction in the default mode network and hyperfunction in the central executive and salience networks leading to their behavioral expression in acting out and enactment in contrast to verbal expression. Thus understood these forms of behavior can make an important contribution to the "talking cure."